Research on the Development of Leisure Fisheries in Shipu Town, China, from the Perspective of Fishing Culture - Li, Jiaolong; Yao, Rong; Qian, Weiguo (International Journal of Natural Resources and Environmental Studies, 2025)
Fishing culture represents a comprehensive survival mode of communities represented by fishermen, developed over human history. It emerged from the survival needs of fishing communities and evolved through the historical processes of fishery farming and animal husbandry. Fishing culture possesses characteristics of universality, dynamism, and integrity, enriched by strong local ethnic features. This paper uses Shipu Town in Ningbo City, Zhejiang Province—a region with typical fishing culture characteristics in China’s coastal areas—as its primary case study. Field investigations reveal that while the fishing culture industry in Shipu Town faces challenges such as the decline of cultural landscapes, weak inheritance, and intense industry competition, leveraging the region’s economic, social, and cultural attributes through effective cultural tourism planning, emphasizing cultural continuity, and driving industry transformation can enable the inheritance, preservation, and promotion of Shipu’s fishing customs and culture.